The Association of Inflammatory Indexes Derived from Peripheral Blood Cell Count and Clinical Signs with Response to Treatment with Dupilumab in Pediatric Patients with Moderate-to-Severe Atopic Dermatitis - Zhang L; Pi J; Wang J; Chen J; Zhang Y; Li J; Wang L; Li Y; Chen A; Luo X; Wang H (Journal of Inflammation Research)
Lingzhao Zhang,1,2 Jiangshan Pi,1,2 Jinsong Wang,3 Jingsi Chen,1 Yunxuan Zhang,1,2 Jie Li,4 Lingling Wang,1,2 Yue Li,1,2 Anwei Chen,1 Xiaoyan Luo,1,5,* Hua Wang1,2,5,* 1Department of Dermatology, Children’s Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Chongqing Key Laboratory of Child Infection and Immunity, Children’s Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 3Department of Gastroenterology, Chongqing Dongnan Hospital, Chongqing, People’s Republic of China; 4Department of Pediatrics, Chongqing Jiangjin District Maternal and Child Health Hospital, Chongqing, People’s Republic of China; 5Ministry of Education Key Laboratory of Child Development and Disorders, Children’s Hospital of Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hua Wang; Xiaoyan Luo, Department of Dermatology, Children’s Hospital of Chongqing Medical University, No. 136 Zhongshan Second Road, Yuzhong District, Chongqing, 400015, People’s Republic of China, Tel +8615123380348, Email huawang@hospital.cqmu.edu.cn; xyluo@hospital.cqmu.edu.cnBackground: Dupilumab is a safe and effective treatment for moderate to severe atopic dermatitis (AD), but real-world data in pediatric patients in China are limited. Currently, there is no exploration of changes in blood cell counts derived indexes in pediatric patients, especially under 6 years old.Purpose: To investigate the changes in blood cell counts derived indexes before and after dupilumab treatment in Chinese children with AD, the relationship with clinical scores, and the potential role of these indexes on treatment efficacy.Patients and Methods: We conducted a retrospective study of 109 children with moderate to severe AD treated with dupilumab. Derived inflammatory indexes, including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), eosinophil-to-lymphocyte ratio (ELR), eosinophil-to-neutrophil Ratio (ENR), monocyte-to-lymphocyte ratio (MLR), inflammation response index (SIRI), systemic inflammation index (SII), and aggregate inflammation systemic index (AISI) were calculated. The correlation between clinical scores and inflammatory indexes at different treatment time points were analyzed. Logistic regression and ROC curve was employed to explore factors associated with treatment efficacy.Results: Baseline ELR and ENR were positively correlated with the baseline Eczema Area and Severity Index (EASI) and the Scoring Atopic Dermatitis (SCORAD). Additionally, baseline ENR levels showed a positive correlation with the baseline Peak Pruritus Numeric Rating Scale (PP-NRS). At 4 and 16 weeks of treatment, the percentage reduction in ELR was significantly associated with the percentage reduction in EASI and PP-NRS. Logistic regression results indicated that high baseline ELR could predict a poor response to dupilumab treatment.Conclusion: ELR was significantly correlated with disease severity score during the treatment with dupilumab. Baseline ELR could act as a predictor of the efficacy of dupilumab in the treatment of children with atopic dermatitis under 6 years of age.Keywords: atopic dermatitis, dupilumab, eosinophil-to-lymphocyte ratio, blood cell count